Midwifery Antenatal Care of Mrs "S" Gestation 38 Week 1 Day with Hypertension in Health Watampone District of Bone - Hasnidar (Jurnal Suara Kesehatan, 2015)
The gestation period is a condition that requires attention, especially the health of mother and fetus or infant, one of which needs to be aware of the pregnant mother is hypertension that occurs in pregnancy, because hypertension in pregnancy is 5-15% complication of pregnancy and is one of three causes The highest maternal mortality and morbidity. In this study applied the approach of midwifery care management process that includes 7 steps Varney namely: basic data collection, identification of diagnosis / actual problem, identification of diagnosis / potential problems, the determination of the need for immediate action or collaboration, develop a plan of care, care management and evaluation. The data collection is done by anamneses / interview with clients, husband, and family to obtain the data needed to provide midwifery care to clients. Method used in arranging this study included library studies, case study by using the approach of midwifery care management process that includes 7 steps Varney namely: basic data collection, identification of diagnosis / actual problem, identification of diagnosis / potential problems, the determination of the need for immediate action or collaboration, develop a plan of care, care management and evaluation. Result indicated that results of the identification data and basic data analysis in the case of Mrs. "S" then obtained complaint mothers often dizziness, headache and have done a physical examination with a blood pressure of 140/90 mmHg results. This is the same with the theory of signs and symptoms of hypertension in pregnant women.